ELearning significantly improves midwives' knowledge of the congenital cytomegalovirus prevention guidelines. (September 2022) - Swinburn, Ms Kath; Sheedy, Hayley Smithers; Waight, Ms Emma; King, Ms Ruth; Hall, Ms Bev; Hui, Lisa; Jones, Cheryl; Daly, Ms Kate; Rawlinson, William; McIntyre, Sarah; Webb, Ms Annabel; Badawi, Nadia; et al.
Abstract : Introduction: Congenital cytomegalovirus (CMV) infection is a preventable cause of neurodevelopmental disability. Australian guidelines recommend pregnant women are informed about CMV hygiene precautions to reduce their risk of infection however less than 10% of maternity health professionals routinely provide such prevention advice. Aim: We developed and evaluated the effectiveness of an eLearning course for midwives to improve knowledge and confidence about CMV. Methods: Participants undertaking the online course through the Australian College of Midwives Learning Management System between March and November 2020 were invited to complete a course evaluation questionnaire; prior to commencing the course (T1), immediately following completion (T2) and three months after completion (T3). A linear mixed model with random intercept was used to evaluate change in participant scores over time, while accounting for within-subject correlation. A p-value of <0.05 was considered statistically significant. Results: 363 midwives (87%), midwifery students (8%) and other nurses (5%) participated. At T1 80% indicated they had not received education about CMV. Total adjusted mean scores for questionnaires completed between T1 (n=363) and T2 (n=238) increased significantly (from 17.2 to 22.8, p<0.001). Limited data at T3 (n=27) indicated that whilst scores were lower than at T2 (-1.7, p<0.001), they remained significantly higher than at T1 (+3.6, p <0.001). Participant's awareness of CMV information resources improved from 10% at T1 to 97% by T2 and 100% at T3. Confidence in providing CMV advice increased from 6% at T1 to 95% at T2 (p<0.001). 99% of participants indicated they would recommend the course to their colleagues. Conclusion: Participants who completed the eLearning course had significantly improved knowledge and confidence in providing advice about CMV. Programs targeting other maternity health professional groups should be considered, to further support the implementation of the congenital CMV prevention guidelines.